The Validity of Electronic Signatures in Providing Evidence in Civil Cases - Mambu, Joupy Gustaf Z (Jurnal Hukum dan Keadilan, 2026)
The development of information technology has encouraged the use of electronic signatures in various civil transactions, but their acceptance as evidence in court still raises legal issues. This study aims to analyze the validity of electronic signatures and their evidentiary power in civil cases in Indonesia. The research method used is normative legal research with a statutory, conceptual, and case approach, through a study of regulations, legal doctrine, and judicial practice. The results of the study indicate that normatively, electronic signatures have been recognized as valid under the Electronic Information and Transactions Law as long as they fulfill the elements of authentication, integrity, and non-repudiation. Conceptually, through the theory of functional equivalence and the theory of evidence law, electronic signatures have an equivalent function to manual signatures in proving the will of the parties. However, in judicial practice, inconsistencies are still found in the acceptance and assessment of their evidentiary power due to unclear norms and a lack of synchronization between material law and formal law. This condition has an impact on legal uncertainty and potential injustice for the parties. Therefore, it is necessary to reformulate civil evidence law through regulatory harmonization, affirmation of evidentiary standards, and increasing the capacity of law enforcement officers so that the use of electronic signatures can be applied consistently and provide certainty, justice, and legal benefits